Análise do perfil de aptidão física, composição corporal e ângulo de fase de praticantes regulares de crossfit® - ARAUJO JUNIOR, João da Hora (2024)
Introduction: CrossFit is a training modality that has been gaining many followers in the last decade mainly due to the wide variety of movements involved as well as the countless possible benefits of its practice. Objective: To investigate the level of physical fitness, body composition and phase angle of regular CrossFit® practitioners. Material and Methods: 63 regular CrossFit® participants (20 men and 43 women) with an average age of 33.8 ± 7.1 years and body weight 75.8 ± 14.1 kilos, underwent tetra bioimpedance testing. polar for analyzing body composition and phase angle, manual dynamometry for analyzing handgrip strength, jumping with counter movement for analyzing lower limb strength/power and VO2 max test. for oxygen consumption. Results: Our sample presented significant values in the variables of percentage of skeletal muscle mass (men: 60% classified as above average and women: 51% above average), in handgrip strength levels (men: 75% above average and women: 77% above average) and oxygen consumption Vo2 max. (men 53% classified as good and 43% excellent, women: 82% good), for the fat percentage values the classification was (men: 25% very bad and 20% excellent, for women: 46% very bad) , jump with counter movement (men: 44% fair and women: 39% good) and phase angle (men: 65% below average and women: 51% below average). A strong positive correlation was observed between the variables of body weight and handgrip (0.7), Vo2 and fat percentage (0.64) and jumping with counter movement and Vo2 (0.60), in addition to a strong negative correlation between the variable’s percentage of fat and percentage of lean mass (-0.79). Conclusion: Our findings indicate that CrossFit® practitioners have a positive physical fitness profile, however, their body composition and phase angle have values outside the recommended range. However, we highlight the importance of knowing this profile to adapt their training to this reality.